Assessment of Groundwater Quality in the Holocene Aquifer in Duy Tien District, Ha Nam Province using Groundwater Quality Index (GWQI) - Tham, Trinh Thi; Thi Hien, Do; Thuy Chung, Nguyen; Tra Mai, Ngo (VNU Journal of Science: Earth and Environmental Sciences, 2022)
This study aims to assess the pollution level of groundwater in the Holocene aquifer in the Duy Tien district, Ha Nam province, using the groundwater quality index (GWQI). Groundwater samples were collected from 20 wells and dug wells in households in rainy and dry seasons. The results showed that many parameters such as ammonium, nitrite, total hardness, chloride, Fe, Mn, Pb, As exceeded the permitted limits according to QCVN 09-MT: 2015/BTNMT. In particular, the ammonium concentrations at all monitoring wells were higher 2,73 ÷ 28,3 times than permitted values. The GWQI ranged between 84 ÷ 369 in the rainy season and 67 ÷ 290 in the dry season, while the proportion of wells with "very poor water" quality in the rainy and dry season was 50% and 65%, respectively. The GWQI values can be a scientific basis for effective use and protecting groundwater resources.